2016
DOI: 10.1088/0264-9381/33/23/235003
|View full text |Cite
|
Sign up to set email alerts
|

Causality and black holes in spacetimes with a preferred foliation

Abstract: Abstract. We develop a framework that facilitates the study of the causal structure of spacetimes with a causally preferred foliation. Such spacetimes may arise as solutions of Lorentz-violating theories, e.g. Hořava gravity. Our framework allows us to rigorously define concepts such as black/white holes and to formalize the notion of a 'universal horizon', that has been previously introduced in the simpler setting of static and spherically symmetric geometries. We also touch upon the issue of development and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 110 publications
(401 reference statements)
4
80
0
Order By: Relevance
“…In Refs. [38,[46][47][48] it is showed that in a LIV scenario, where there are different horizons for particles with different energies, there is a violation of the second law of the black hole thermodynamics making possible a construction of a perpetuum mobile (see however [49] for a possible resolution of this problem). We see that in contrast with LIV scenarios, in our case there is a unique horizon, which is consistent with the fact that in DSR framework there is a relativity principle.…”
Section: B Event Horizonmentioning
confidence: 99%
“…In Refs. [38,[46][47][48] it is showed that in a LIV scenario, where there are different horizons for particles with different energies, there is a violation of the second law of the black hole thermodynamics making possible a construction of a perpetuum mobile (see however [49] for a possible resolution of this problem). We see that in contrast with LIV scenarios, in our case there is a unique horizon, which is consistent with the fact that in DSR framework there is a relativity principle.…”
Section: B Event Horizonmentioning
confidence: 99%
“…A further generalization to spacetimes with a preferred foliation (1.1) was carried out systematically [24], and shown that, among other things, the zeroth law of black hole mechanics holds at universal horizons.…”
Section: Introductionmentioning
confidence: 99%
“…V A-V C? We looked for a first law in the form (1). The fourdimensional asymptotically flat case is encouraging, because the proportionality between S UH and the area of the UH suggests that T-theory respects a form of holographic principle.…”
Section: Discussionmentioning
confidence: 99%